Chitosan improves the chemical composition, microbiological quality, and aerobic stability of sugarcane silage - Gandra, J. R.; Oliveira, E. R.; Takiya, C. S.; Goes, R. H.T.B.; Paiva, P. G. [UNESP]; Oliveira, K. M.P.; Gandra, E. R.S.; Orbach, N. D.; Haraki, H. M.C. (Elsevier, 2016)
The purpose of the current study was to evaluate the effects of inoculants on chemical composition, dry matter (DM) and neutral detergent fiber (aNDF) in vitro degradation, fermentative and effluent losses, microbiology, fermentative profile, and aerobic stability of sugarcane mini-silos. Treatments were randomly distributed to the mini-silos, in which: (1) Control (CON); (2) Lactobacillus buchneri (Lb), addition of Lb at 2.6 × 1010 cfu/g; (3) Lactobacillus buchneri and Bacillus subtilis (Lb + Bs), addition of Lb at 2.6 × 1010 cfu/g and Bs at 1 × 109 cfu/g; and (4) Chitosan (CHI), addition of 1% of CHI on wet basis of sugarcane ensiled. Treatments 2 and 3 were incorporated to the silage at 2 g/t of natural matter ensiled. Lb and Lb + Bs did not alter the in vitro degradation of DM and NDF. Chitosan incorporation increased the DM content (P = 0.013, 18.7 g/kg DM) and improved (P = 0.029, 45.6 g/kg DM) the NDF in vitro degradation of sugarcane silage. In addition, CHI incorporation showed higher (P = 0.002) DM content in silage than Lb and Lb + Bs. Microbial inoculants (Lb and Lb + Bs) reduced the total losses (P = 0.009) of sugarcane silage. Moreover, CHI incorporation showed lower (P = 0.001, 84.9 g/kg DM) total losses and higher (P = 0.031, 84.8 g/kg DM) dry matter recovery than Lb and Lb + Bs. Lactic acid bacteria concentration was increased (P = 0.001) with additives, and CHI incorporation showed higher (P = 0.001) lactic acid bacteria concentration than silages treated Lb and Lb + Bs. All additives decreased the ethanol concentration in sugarcane silage, but CHI showed lower (P = 0.002) ethanol concentration compared to Lb and Lb + Bs. Inoculants improved the aerobic stability of sugarcane silage. In general, the incorporation of CHI to sugarcane silage showed better results of NDF in vitro degradation and gas and effluent losses than Lb and Lb + Bs. Moreover, CHI incorporation showed higher concentration of lactic acid bacteria and lower concentration of ethanol compared to silages treated Lb and Lb + Bs. Chitosan may be an alternative additive to microbial inoculants used in sugarcane ensiling.
Keywords: Aerobic stability; Bacillus subtilis; Chitin; Fermentation; Inoculant; Lactobacillus buchneri